2021
DOI: 10.1186/s12960-021-00642-8
|View full text |Cite
|
Sign up to set email alerts
|

The physiotherapy workforce in the Brazilian Unified Health Care System

Abstract: Background Maintaining sufficient health care workforce is a global priority to achieve universal health coverage. Therefore this study addresses the availability of physiotherapists in Brazil. Objective To describe secular trends of the physiotherapy workforce-to-population ratio in the Unified Health System, considering public and private sector and care level (primary, secondary, tertiary) in Brazil and its regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Resultantly, vacant rehabilitation posts are frozen, and therapists are forced to seek employment in the private sector or overseas [10]. Similar trends have been noted in other upper middle-income countries such as Brazil [26,30]. These low ratios show disparities in the rehabilitation workforce at all levels of care.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Resultantly, vacant rehabilitation posts are frozen, and therapists are forced to seek employment in the private sector or overseas [10]. Similar trends have been noted in other upper middle-income countries such as Brazil [26,30]. These low ratios show disparities in the rehabilitation workforce at all levels of care.…”
Section: Discussionmentioning
confidence: 71%
“…Population adjusted ratios are routinely reported as a metric to describe the rehabilitation workforce density [24][25][26][27]. This study showed alarmingly low population-adjusted ratios of the total number of therapists in each of the three provinces per uninsured population (see Table 6).…”
Section: Discussionmentioning
confidence: 82%
“…Fifth, Nepal has only 1 physiotherapist per 25,000 people, which is fewer than India (1:12,111), Thailand (1:15,942) and Brazil (1:2337), but higher compared to other middle‐income countries such as Bangladesh (1:183,475) and Sri Lanka (1:28,247). 14 , 39 The smaller number of physiotherapists in these countries impedes the quality of physiotherapy care for those in need of comprehensive rehabilitation and hinders the recommendation by World Health Organisation to strengthen the multidisciplinary rehabilitation workforce for the future. 8 , 40 The lower number of physiotherapists in Nepal is attributed to the short history of a physiotherapy degree in Nepal and physiotherapists' migration, mostly to high‐income countries for employment and education.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may have impacted hospitalized patients with COVID-19 was the lack of adequately trained healthcare professionals. Many physicians, nurses, and physiotherapists working in ICU were not board-certified by the specialty [ 37 , 38 ]. Moreover, it is also likely that better equipment, effective and expensive drugs were more available in private than public services.…”
Section: Discussionmentioning
confidence: 99%